Posicionamento por ponto preciso com solução de ambiguidades inteiras no contexto de rede GPS - Lima, Chaenne Milene Dourado Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Integer ambiguity resolution is a challenger theme that has been very much researched, mainly to precise GNSS applications in Geodynamic and Geodesy. Among several GNSS positioning methods, PPP has presented itself as a powerful tool useful for many applications and it has been of interest in scientific as in operational applications. Researches at global level have been carried out in context of PPP integer ambiguity resolution, aiming to improve the accuracy for short observation period, or even instantly. This PhD thesis goal is to investigate and adopt a methodology for PPP integer ambiguity resolution. Additionally, it is intended to develop, improve and perform the necessary changes, in terms of algorithm, to implement a computational program that allows to run the PPP method using fixed ambiguities based on a GNSS network. After some studies and investigations, the adopted methodology in this thesis is based on the estimative of WL (wide-lane) and NL (Narrow-lane) simple difference ambiguity (SD) to remove the receiver UPDs (Uncalibrated phase delays) that are present in the ambiguities of the carrierphase. SD ambiguities were combined in a GNSS network in order to compute the satellite UPDs. WL e NL UPDs for the satellites, estimated at the level of simple difference, were applied to fix the ambiguities of the ion-free linear combination at the user level, by means of constraints to improve the quality of the parameters estimative based on PPP. In order to reach the main goal of this research, a software called UPD_NETWORK was developed to estimative the UPD of the satellite pair in the GNSS network. Furthermore, adaptations were applied to the RT_PPP software algorithms to allow it performing PPP with integer ambiguity instead of float ambiguity estimative...

A solução de ambiguidades inteiras é um assunto desafiador e muito pesquisado, principalmente para aplicações GNSS na Geodésia e Geodinâmica. Dos métodos de posicionamento GNSS, o PPP tem-se demonstrado como uma poderosa ferramenta para diversas aplicações e tem sido alvo de interesse, tanto em pesquisas científicas quanto em aplicações práticas. Estudos em nível mundial têm sido realizados no contexto da solução das ambiguidades inteiras no PPP, com a finalidade de melhorar a acurácia em curtos períodos de observação, ou até mesmo de forma instantânea. Esta pesquisa tem como objetivos investigar e adotar uma metodologia para solução de ambiguidades inteiras, além de desenvolver, aperfeiçoar e realizar as alterações necessárias em termos de algoritmos, para que a mesma seja programada computacionalmente de forma que se possa realizar o método PPP com ambiguidades fixas, com base em uma rede de estações GNSS. Após estudos e investigações, a metodologia adotada nesta tese consiste na estimativa das simples diferenças (SD) de ambiguidades WL (wide-lane) e NL (narrow-lane) para remover os UPDs (uncalibrated phase delays) do receptor, presentes nas ambiguidades da fase da onda portadora. Esses valores de SD de ambiguidades foram combinados dentro de uma rede de estações GNSS para calcular os UPDs dos satélites. Os UPDs WL e NL referentes aos satélites, estimados em nível de SD, foram aplicados para fixação inteira das ambiguidades da combinação linear ionfree em nível do usuário, onde são introduzidas equações de injunção para as ambiguidades conhecidas visando melhorar a estimativa dos parâmetros no PPP. Para atingir os objetivos da pesquisa, foi desenvolvido um software, chamado UPD_NETWORK, para estimativa dos UPDs, para um determinado par de satélites dentro da rede GNSS...
Keywords: Cartografia; Ambiguidade; Geodesia; Geodinamica; Sistemas de navegação global por satélite; Cartography